Efficacy of a Web-Enabled, School-Based, Preventative Intervention to Reduce Bullying and Improve Mental Health in Children and Adolescents: Study Protocol for a Cluster Randomized Controlled Trial - Díaz-Caneja, Covadonga M.; Martín-Babarro, Javier; Abregú-Crespo, Renzo; Huete-Diego, Miguel Á.; Giménez-Dasí, Marta; Serrano-Marugán, Isabel; Arango, Celso (Frontiers in Pediatrics, 2021)
Introduction: Bullying is a major preventable risk factor for mental disorders. Available evidence suggests school-based interventions reduce bullying prevalence rates. This study aims to test the efficacy of a web-enabled, school-based, multicomponent anti-bullying intervention to prevent school bullying and to assess its effects on mental health and quality of life. Methods and analysis: Cluster randomised controlled trial conducted in 20 publicly funded primary and secondary schools in Madrid, Spain. Schools are randomly allocated to either the intervention arm (n=10) or conventional practices arm (n=10). The web-enabled intervention (LINKlusive) lasts approximately 12 weeks and consists of three main components: i) an online training programme for teachers and parents, ii) a web-guided educational programme for students, focusing on promoting respect for diversity, empathy, and social skill development, and iii) a web-guided, teacher-delivered, targeted intervention programme for bullying situations identified based on peer-support strategies and individual intervention for those involved (i.e. bullying victims and perpetrators). The primary objective is to compare differences between peer-reported bullying victimisation in the intervention and control arms at the end of the intervention. Secondary outcome measures are additional measures of bullying victimisation and perpetration, mental health symptoms, self-esteem, and quality of life. A follow-up assessment is conducted one year after the end of the intervention. Treatment effects will be tested using multilevel mixed models, adjusting for school-, classroom-, and student-related covariates. Considering the increased bullying rates in children with special educational needs, a specific subgroup analysis will test the efficacy of the intervention on bullying prevalence, mental health, and quality of life in this particularly vulnerable population. Ethics and dissemination: The Deontology Commission of the School of Psychology, Universidad Complutense in Madrid, Spain reviewed the study protocol and granted ethical approval on 21st January 2019. The results of the trial will be disseminated in relevant peer-reviewed journals and at conferences in the field. Trial registration number: ISRCTN15719015